2022
DOI: 10.1177/09544062221080034
|View full text |Cite
|
Sign up to set email alerts
|

A thermophysical modelling of electric discharge coating process

Abstract: This research paper presents a thermophysical model development and simulation of the electric discharge coating process (EDC). Many literatures are available for the electric discharge coating process from an experimental perspective. A 2-D axisymmetric model was initially developed with the realistic assumption with multi-spark overlap conditions considered in this work. The melt pool volume of the tool material is estimated from the 2D model. The 3D coating model was developed using COMSOL Multiphysics 5.4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is observed that when the current increases, coating thickness increases. The plasma radius and melt pool volume depend on power density at the tool surface [15]. So, an increase in current enhances tool wear and material deposition rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that when the current increases, coating thickness increases. The plasma radius and melt pool volume depend on power density at the tool surface [15]. So, an increase in current enhances tool wear and material deposition rate.…”
Section: Resultsmentioning
confidence: 99%
“…Muralidharan B et al [14] analyzed the relation between the input process parameters and the response of the EDC process with empirical and mathematical models. Kumaran V et al [15] developed a thermophysical model with COMSOL Multiphysics for the EDC process to understand the mechanism of the coating process. Solid lubricants are applied in harsh conditions with high vacuum and elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Algodi SJ et al [29] developed a single spark modelling to analyze the EDC process on crater formation and the transfer of heavy species material from the tool electrode. Kumaran V et al [30] developed a thermophysical model to analyze the EDC mechanism with multi-spark phenomena and reported an error factor of coating thickness between a range of 4% to 14% compared to experimental studies.…”
Section: Heat Treatment and Chemical Treatment Are Requiredmentioning
confidence: 99%
“…Lee C et al [30] detailly investigate the effectiveness of nitride coating on steel substrates by scratch test and the result shows that coated substrates have better tribological properties. Kumaran V et al [31] developed a simulation model to better understand the coating phenomenon in the electric discharge coating process. This model showed that both the pulse duration and current had a significant impact on the coating thickness.…”
Section: Introductionmentioning
confidence: 99%